CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film